2012 IEEE Colloquium on Humanities, Science and Engineering (CHUSER) 2012
DOI: 10.1109/chuser.2012.6504292
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic ultrasound exposure during pregnancy potentially affects rabbit fetal parathyroid hormone level

Abstract: Prenatal hyperparathyroidism (HPT) is one of the true emergency cases and capable of causing serious problems to the mother as well as the unborn baby. This in-vivo study was aimed to investigate the changes in parathyroid hormone (PTH) level of rabbit fetal bodies exposed to diagnostic ultrasound during pregnancy for varying duration of time. As compared to that of control, significantly low PTH levels were observed in the groups exposed for 30 and 60 minutes during pregnancy. This ultrasound heating effect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In the study by Ang et al (12), the authors found that the distribution of neurons of the cerebral neocortex in newborn mice differed significantly from control mice on the 10th day after birth when exposed to ultrasound wave for a total of 30 min or longer during the period of neuronal migration. Md Dom et al (13) suggested that parathyroid hormone (PTH) levels in rabbit fetal bodies exposed to ultrasound at different gestational stages were significantly decreased. A study on human chorionic villi indicated that the cleavage products of active caspase-3 and cytochrome c release were significantly increased in a time-dependent manner when exposed to transvaginal ultrasound in the first trimester of pregnancy (14).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Ang et al (12), the authors found that the distribution of neurons of the cerebral neocortex in newborn mice differed significantly from control mice on the 10th day after birth when exposed to ultrasound wave for a total of 30 min or longer during the period of neuronal migration. Md Dom et al (13) suggested that parathyroid hormone (PTH) levels in rabbit fetal bodies exposed to ultrasound at different gestational stages were significantly decreased. A study on human chorionic villi indicated that the cleavage products of active caspase-3 and cytochrome c release were significantly increased in a time-dependent manner when exposed to transvaginal ultrasound in the first trimester of pregnancy (14).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the hormonal assay of total triiodothyronine (tT3) and total thyroxine (tT4) showed a numerical reduction but not statistically significant in the insonated group as compared to the non-insonated; ultrasound heating may have some effect on thyroid hormonal level. Dom et al (2013) reported a significantly lowered parathyroid hormone level in the insonated group as against the noninsonated. This could possibly be because there was an increase in the time of exposure (60minutes) as against the time of exposure in this study (5 minutes).…”
Section: Discussionmentioning
confidence: 93%
“…In fetal physiological development, formation of thyroid glands begins at the middle till the end stage of gestation (Terranova, 2009). Hence, any external disruption like ultrasound heating could possibly affect the development of the glands, thus its secretion (Dom et al, 2013). There are two basic mechanisms, thermal and non-thermal, by which ultrasound is known to affect biologic materials (Ndumbe et al, 2008;Sheiner & Abramowicz 2008;Brendt, 1986;Sikov, 1986a;Sikov, 1986b;Laurel, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to a placentation disorder resulting from suboptimal nutrients transferred to a fetus [28]. In another in vivo study by Dom et al [30] the differences in fetal parathyroid hormone level in ultrasound exposed and non-ultrasound exposed group could lead to a possible result in alteration of physiological developments of fetus. This will cause various physiological variables alteration, not limited to reduction in fetal weight which was reveled in this study.…”
Section: Discussionmentioning
confidence: 99%